Societal perceptions towards the hearing impaired and their psychological implications - Matlala, Mahlogonolo Maureen (University of Limpopo, 2013)
The study is aimed at investigating societal perception towards the hearing impaired and their psychological implications. The study concentrated on how the hearing impaired thought the hearing public perceived them and, also identified the psychological implications of these (perceived) societal perceptions on the hearing impaired. The research design is qualitative in nature, wherein, a convenient and purposive sample of ten hearing-impaired participants was used. Video recorded interviews of open-ended questions and questionnaires were used in combination to gather information. The Interpretative Phenomenological Analysis (IPA) was applied as the method of data analysis. Three super-ordinate themes were identified. These themes primarily indicated that the hearing impaired hold the view that they are negatively perceived by the hearing society. The findings of the study were that negative societal perceptions result in negative self-perceptions and discourage social interactions between the hearing impaired and the hearing communities.
Thesis (M.A. (Clinical Psychology)) --University of Limpopo, 2013
Keywords: Societal perception; Hearing impaired; Psychological implications; Deafness psychological aspects; 305.9082; Hearing impaired; Clinical psychology; Social perception; Research - Psychological aspects